Mental health professionals' feelings and attitudes towards coercion. (January 2021) - Morandi, Stéphane; Silva, Benedetta; Mendez Rubio, Monserrat; Bonsack, Charles; Golay, Philippe
Abstract: Background: Despite absence of clear evidence to assert that the use of coercion in psychiatry is practically and clinically helpful or effective, coercive measures are widely used. Current practices seem to be based on institutional cultures and decision-makers' attitudes towards coercion rather than led by recommendations issued from the scientific literature. Therefore, the main goal of our study was to describe mental health professionals' feelings and attitudes towards coercion and the professionals' characteristics associated with them. Method: Mental health professionals working in the Department of Psychiatry of Lausanne University Hospital, Switzerland, were invited to participate to an online survey. A questionnaire explored participants' sociodemographic characteristics, professional background and current working context, and their feelings and attitudes towards coercion. Exploratory Structural Equation Modelling (ESEM) was used to determine the structure of mental health professionals' feelings and attitudes towards coercion and to estimate to which extent sociodemographic and professional characteristics could predict their underlying dimensions. Results: 130 mental health professionals completed the survey. Even if a large number considered coercion a violation of fundamental rights, an important percentage of them agreed that coercion was nevertheless indispensable in psychiatry and beneficial to the patients. ESEM revealed that professionals' feelings and attitudes towards coercion could be described by four main dimensions labelled "Internal pressure", "Emotional impact", "External pressure" and "Relational involvement". The personal as well as the professional proximity with people suffering from mental disorders influences professionals' feeling and attitudes towards coercion. Conclusions: As voices recommend the end of coercion in psychiatry and despite the lack of scientific evidence, many mental health professionals remain convinced that it is a requisite tool beneficial to the patients. Clinical approaches that enhance shared decision making and give the opportunity to patients and professionals to share their experience and feelings towards coercion and thus alleviate stress among them should be fostered and developed.